On the Lebesgue Summability of Multiple Trigonometric Series - Bagota, Mónika; Móricz, Ferenc (Sarajevo Journal of Mathematics, 2024)
The Lebesgue summability of a trigonometric series is defined in terms of the symmetric differentiability of the sum of the formally integrated trigonometric series in question. In this paper we extend the theorems of Fatou and Zygmund from single to multiple trigonometric series. 2000 Mathematics Subject Classification. 42A24, 42B08